2018
DOI: 10.1002/jcb.26800
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐326 and microRNA‐200c: Two novel biomarkers for diagnosis and prognosis of pediatric acute lymphoblastic leukemia

Abstract: Multidrug resistance (MDR) is considered as the major obstacle for treating pediatric acute lymphoblastic leukemia (ALL). MicroRNAs (miRNAs) are small non coding RNAs which may potentially regulate response to chemotherapy. In this study, total RNA was isolated from bone marrow samples of 46 children with de novo ALL and 16 controls. Quantitative reverse transcriptase polymerase chain reaction was used to investigate the expression profile of the predicted miRNAs; miR-326 and miR-200c, and their predicted targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 38 publications
5
35
0
Order By: Relevance
“…In addition to ABCC144, miR-326 also negatively regulated other ABC family members such as ABCA2 and ABCA3, which are drug-resistance related genes [200]. However, the miR-326 expression is reported to be significantly downregulated in the multidrug resistance (MDR+) pediatric ALL patients compared to the (MRD-) group [27]. A recent study showed upregulation of miR-125b-2 cluster (Let-7c, miR-125b, and miR-99a) in leukemia patients with ETV6-RUNX1 + fusion gene expression.…”
Section: Underlying Mechanisms Of Chemoresistance Regulated By Ncrnasmentioning
confidence: 99%
“…In addition to ABCC144, miR-326 also negatively regulated other ABC family members such as ABCA2 and ABCA3, which are drug-resistance related genes [200]. However, the miR-326 expression is reported to be significantly downregulated in the multidrug resistance (MDR+) pediatric ALL patients compared to the (MRD-) group [27]. A recent study showed upregulation of miR-125b-2 cluster (Let-7c, miR-125b, and miR-99a) in leukemia patients with ETV6-RUNX1 + fusion gene expression.…”
Section: Underlying Mechanisms Of Chemoresistance Regulated By Ncrnasmentioning
confidence: 99%
“…Furthermore, we demonstrated downregulation of miR-335-3p in the chALL MDR patients (58 B-ALL and 6 T-ALL). Interestingly, our data revealed that, there is a possibly causative correlation between the downregulation of miR-326 and miR-335-3p, increased risk of drug resistance and ALL relapse, and upregulation of ABCA2 and ABCA3 transporters, respectively (97,106).…”
Section: Mirna Levels Alterationmentioning
confidence: 68%
“…MicroRNAs, recently discovered non-coding endogenous single-stranded RNAs (composed of 19-24 nucleotides), show dysregulation during hematopoiesis and thereby have role in leukemogenesis (14,94). These micro markers have proven to be very promising chALL biomarkers and have widespread clinical applications because of their stability and resistance to degradation in not only blood, but also various biological specimens (such as tissue, sputum, stool and formalin-fixed paraffin-embedded (FFPE) specimens), easily measured, and most importantly, their quantities correlates with the presence of the malignancy or with clinically relevant malignancy features (8,14,(95)(96)(97). Recent studies have revealed that extracellular circulating miRNA levels in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids can be used as biomarkers to diagnose, classify and predict prognosis of chALL (96,(98)(99)(100)(101).…”
Section: Mirna Levels Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, in the AML patients, increased expression level of SALL4 results in drug resistance and poor prognosis through regulating the expression of the ATP-binding cassette (ABC) drug transports, such as ABCG2 and ABCA3. 9,18 Nevertheless, with the general lack of studies about SALL4 expression and its correlation with ABC transporter genes, there is little information about the role of this gene in the biological behavior of childhood ALL and its correlation with MDR and relapse.…”
Section: Introductionmentioning
confidence: 99%